2019
DOI: 10.1186/s12933-019-0967-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta blocker use and type on hypoglycemia risk among hospitalized insulin requiring patients

Abstract: BackgroundAlthough beta blockers could increase the risk of hypoglycemia, the difference between subtypes on hypoglycemia and mortality have not been studied. This study sought to determine the relationship between type of beta blocker and incidence of hypoglycemia and mortality in hospitalized patients.MethodsWe retrospectively identified non-critically ill hospitalized insulin requiring patients who were undergoing bedside glucose monitoring and received either carvedilol or a selective beta blocker (metopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 48 publications
0
26
0
4
Order By: Relevance
“…A retrospective analysis was recently conducted on hospitalized diabetic patients who were taking beta‐blockers, either carvedilol or the selective beta‐blockers, metoprolol or atenolol, to examine whether the use of beta‐adrenergic blockers was associated with increased incidence of hypoglycaemia 49 . The study reported that diabetic patients who were not on basal insulin therapy had increased odds of hypoglycaemia and this ration was greater for the selective beta‐blockers compared to carvedilol.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis was recently conducted on hospitalized diabetic patients who were taking beta‐blockers, either carvedilol or the selective beta‐blockers, metoprolol or atenolol, to examine whether the use of beta‐adrenergic blockers was associated with increased incidence of hypoglycaemia 49 . The study reported that diabetic patients who were not on basal insulin therapy had increased odds of hypoglycaemia and this ration was greater for the selective beta‐blockers compared to carvedilol.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is minimal evidence for supporting the establishment that beta-blockers can be routinely contraindicated in diabetes since they have few clinically essential effects on hypoglycemia recovery and unawareness. Symptoms such as sweating might be improved even though some hypoglycemia signs including palpitation and tremor might be blunted [ 32 35 ]. The reason is that sweating is a sympathetic cholinergic reaction to hypoglycemia, which cannot be repressed by beta-blockers, and cautious use of beta-blockers improves sympathoadrenal activation by hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…There is an association between RAS blockers and hypoglycemia in patients with diabetes 27 , and between beta-blockers and hypoglycemia in hospitalized patients with diabetes acutely managed with insulin 28 . Betablockers reduce hepatic gluconeogenesis and reduce glycogenolysis but the mechanism of hypoglycemia with RAS blockers is unknown.…”
Section: Discussionmentioning
confidence: 99%